2012
DOI: 10.1002/hed.23041
|View full text |Cite
|
Sign up to set email alerts
|

Role of excision repair cross‐complementation 1 expression as a prognostic marker for response to radiotherapy in early‐stage laryngeal cancer

Abstract: Background and Purpose Tumors with high expression of excision repair cross complementation 1 (ERCC1) are resistant to platinum-based chemotherapy or chemoradiotherapy. We evaluated the prognostic value of ERCC1 expression in a cohort of laryngeal cancer treated with radiotherapy alone, to determine if expression correlated with clinicopathologic risk factors, local control, or overall survival. Material and Methods The study included 123 patients with stages I – II laryngeal squamous cell carcinoma treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…There is a considerable heterogeneity between reported results in head and neck patients. Whereas the literature on ERCC1 and radiotherapy is very scarce and the evidence for that relation has not been robust especially in clinical settings, we think it is of great importance to analyze separately treatments including platinum-based chemotherapy and radiotherapy alone [35][36][37]. Besides it was reported that although ERCC1 positive cells showed increased chemoresistance they might have been particularly radiosensitive and less hypoxic [38].…”
Section: Discussionmentioning
confidence: 97%
“…There is a considerable heterogeneity between reported results in head and neck patients. Whereas the literature on ERCC1 and radiotherapy is very scarce and the evidence for that relation has not been robust especially in clinical settings, we think it is of great importance to analyze separately treatments including platinum-based chemotherapy and radiotherapy alone [35][36][37]. Besides it was reported that although ERCC1 positive cells showed increased chemoresistance they might have been particularly radiosensitive and less hypoxic [38].…”
Section: Discussionmentioning
confidence: 97%
“…Higher expression levels of ERCC1 have been correlated with worse outcomes in multiple malignancies including breast, head and neck, esophageal, gastric, colorectal, ovarian, and lung cancers ( 9 16 ). However, in NSCLC, the majority of work investigating ERCC1 has been to elucidate its impact in individuals who received treatment with chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[53]. UPR induction as a radiosensitizer has also been discussed extensively in brain, lung and pancreatic cancer cell lines [54][55][56].…”
Section: Agents Impacting the Uprmentioning
confidence: 99%